Used of Thalassina anomala Protein Hydrolysate with Enzymatic Processes for Fortification in Instant Porridge - Paridah Hasibuan; Suparmi Suparmi; Tjipto Leksono (Jurnal Perikanan dan Kelautan, 2024)
This research aims to discover the characteristics of Thalasina anomala protein hydrolysate fortification with instant porridge. The method used in this research is an experimental procedure with a completely random design. The research was conducted in 2 stages. Stage 1 is the production of shrimp protein hydrolysate with the enzymatic process, namely papain enzymes with concentration levels (10, 15, and 20%); the observed parameters are the chemical composition of meat, shrimp protein hydrolysis, and total amino acids. Protein hydrolysis results in stage 1 as a fortification raw material in stage 2, which produces instant powder with treatment (0%,5%, and 10%). The parameters tested include the chemical composition of shrimp protein hydrolysate fortifications with instant powder, water absorption, and powder solubility. The study results showed that the protein content of the shrimp meat is 84.98% (dw). The characteristic of the protein is produced using yellow-white papain enzymes with protein content of A1=77.44%, A2=80.56%, and A3=84.56% (dw). The degree of hydrolyze produced is A1 = 56.34 %, A2 = 64.51 %, and A3 = 69.19%. Shrimp protein hydrolysate contains amino acids with a total of 12.25%. Protein hydrolysis fortified with instant porridge produces organoleptic characteristics such as appearance B0=5.4, B1=5.3 B2=5,3, flavor B0 = 5.1, B1= 5.2 B2 = 5.0, Taste B0=4.8, B1=5,5 B2=5.8, and Textures B0=3.2, B1=3.6 B2=4.4. The chemical composition of shrimp protein hydrolysis fortified with instant porridge showed protein content is B0= 9.59%, B1= 18.56%, and B2= 22.54% (dw), with the absorption of water produced, is B0=4.68% B1=5.31% and B2=6.08%, and the solubility of the instant porridge produced B0=43.58%, B1=37.21% B2=33.46%.